Diyanet İşleri Başkanlığı Dinî yüksek ihtisas kurslarında verilen hadis derslerine dair bazı mülahazalar - Dinçoğlu, Mehmet (My University, 2013)
Diyanet İşleri Başkanlığı, İslamî ilimler alanında yetkin ve sahasına hAkim din görevlileri yetiştirmek amacıyla altı eğitim merkezinde Dinî Yüksek İhtisas Kursları düzenlemektedir. Otuz ay süreli ihtisas kursunda verilen eğitimin ilk dokuz aylık Arapça hazırlık bölümünü başaran kursiyerlere, Kuran-ı Kerîm, Tefsir, Hadis, Fıkıh, İslam Düşüncesi alanlarında dersler verilmektedir. İhtisas kurslarındaki önemli alan derslerinden biri de hadis dersleridir. Makale, kuruluşundan günümüze kadar ihtisas eğitiminde verilen hadis dersleri ve müfredatına dair bazı mülahazalar içermekte, bu çerçevede hadis eğitimi ve öğretiminin daha verimli şekilde yapılabileceğine dair bazı öneriler sunmaktadır.

Presidency of Religious Affairs has been organizing Religious High Specialization Courses in six education centers to educate staff qualified in Islamic sciences and knowledgeable in his/her field. In this thirty-month-period specialization course, courses in the fields of Quran recitation, Exegesis, Hadith, Islamic Law (Fiqh) and Islamic Thought have been taught to the trainees who were successful in Arabic prep-classes in the first nine-monthperiod of this course. One of the important field lessons of specialization courses is hadith lessons. This article discusses the hadith lessons in specialized education from the beginning till today and hadith curriculum. In this framework, it presents some suggestions on how more efficient hadith education and teaching can be performed.
Some considerations on hadith lessons offered in the courses of Religious High Specialization under the Presidency of Religious Affairs
Keywords: Din Bilimi